Психологічний аналіз долаючої поведінки у чоловіків та жінок зрілого віку - Білюченко, Ю. М.; Biliuchenko, Yu. M. (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Психологія. – 2022. – Т. 33 (72), № 2. - С. 139-144, 2022)
Визначено специфіку стратегій долаючої поведінки у чоловіків та жінок зрілого віку. Вибірку становили чоловіки та жінки від 39 до 55 років в кількості 80 осіб. Емпірично встановлено, що чоловіки та жінки виявляють статистично значущі відмінності за стратегіями долаючої поведінки. Визначено, що жінки схильні до пошуку соціальної підтримки в стресових ситуаціях, характеризуються стремління поділитися своїми хвилюваннями з іншими людьми, обговорити з ними ситуацію, знайти в них співчуття й розуміння. У групі чоловіків були встановлені високі показники схильності до агресивних дій, направлених на інших людей, які проявляються в тенденції відчувати негативні почуття при невдачах чи конфліктах з іншими людьми, вони можуть звинувачувати оточуючих в будь-чому, відчувати почуття гніву, дратівливості, внутрішнього напруження, розчарування, незадоволеності. У обидвох групах визначена висока конструктивність при подоланні труднощів.

The article highlights the scientific work of scientists on the specifics of coping strategies, taking into account gender differences. Domestic and foreign works portray coping behavior as a constructive strategy in overcoming difficulties and stressors, which has a positive impact on mental health and well-being. The purpose of the study is to determine the specifics of coping strategies in men and women of mature age. The sample consisted of men and women aged 39 to 55 in the number of 80 people. The first group consisted of mature men, and the second group included mature women. The total number of participants in each group was 40 people. Both groups of subjects are individuals who do not have a common occupation and are representatives of different professions. To achieve this goal, the personal questionnaire «SACS» by S. Hobfoll in the adaptation of N. Vodopyanova was used. It is empirically established that men and women show statistically significant differences in coping strategies. It is determined that women tend to seek social support in stressful situations, are characterized by a desire to share their concerns with other people, discuss the situation with them, find compassion and understanding in them. Impulsive actions are characteristic of a group of women, which indicates their tendency to act on the first awakening, under the influence of external circumstances or emotions, without prior consideration of their actions. Also, women are able to intentionally or covertly motivate another person to experience certain conditions, make decisions and perform actions necessary to achieve the initiator’s own goals. The group of men was found to be highly prone to aggressive actions directed at other people, which tends to feel negative feelings in failures or conflicts with other people, they can blame others for anything, feel feelings of anger, irritability, inner tension, frustration, dissatisfaction. In both groups, high constructiveness in overcoming difficulties was determined.

Определена специфика стратегий преодолевающего поведения у мужчин и женщин зрелого возраста. Выборку составляли мужчины и женщины от 39 до 55 лет в количестве 80 человек. Эмпирически установлено, что мужчины и женщины обнаруживают статистически значимые отличия по стратегиям преодолевающего поведения. Определено, что женщины склонны к поиску социальной поддержки в стрессовых ситуациях, характеризуются стремлением поделиться своими волнениями с другими людьми, обсудить с ними ситуацию, найти у них сочувствие и понимание. В группе мужчин были установлены высокие показатели склонности к агрессивным действиям, направленным на других людей, которые проявляются в тенденции испытывать негативные чувства при неудачах или конфликтах с другими людьми, они могут обвинять окружающих в чем-либо, испытывать чувство гнева, раздражительности, внутреннего напряжения, разочарование, недовольство. В обеих группах определена высокая конструктивность при преодолении затруднений.
Psychological analysis of overcoming behavior in of men and women of the mature age
Білюченко, Ю. М. Психологічний аналіз долаючої поведінки у чоловіків та жінок зрілого віку / Білюченко Ю. М. // Вчені записки ТНУ імені В. І. Вернадського. Сер.: Психологія. – 2022. – Т. 33 (72), № 2. - С. 139-144. - DOI: https://doi.org/10.32838/2709-3093/2022.2/23.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; долаюча поведінка; coping behavior; преодолевающее поведение; агресивність; aggressiveness; агрессивность; гендер; gender; зрілий вік; mature age; зрелый возраст; стратегії поведінки; behavioral strategies; стратегии поведения; жінки; women; женщины; чоловіки; men; мужчины